The impact of digital organizational culture and digital capability on organizational performance through digital innovation mediation in the COVID-19 era : a study on Indonesian pharmaceutical SOEs - Muhammad Jasrif Teguh; Noermijati Noermijati; Wahdiyat Moko; Rofiaty Rofiaty (Penerbit Universiti Kebangsaan Malaysia, 2022)
The COVID-19 pandemic has negatively impacted the performance of pharmaceutical companies and must be addressed appropriately. This study aims to determine how digital organizational culture, digital capability, and digital innovation impact organizational performance. The partial least squares structural equation modeling (PLS-SEM) was utilized to analyze the data obtained from 238 respondents affiliated with Indonesian pharmaceutical state-owned enterprises (SOEs). The results of this study suggest that while digital organizational culture does not directly affect organizational performance, it does so indirectly through digital innovation, which acts as a mediating variable. Second, digital capability affects organizational performance directly as well as indirectly through digital innovation. This study empirically provides confirmation of how organizational performance is achieved in pharmaceutical companies, especially during the COVID-19 era. In addition, the findings show some substantial implications for management by focusing on digital organizational culture and digital capability as fundamental predictors of organizational performance through digital innovation.